2010
DOI: 10.1002/jbm.a.32703
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of a biomimetic composite scaffold for bone defect repair

Abstract: For successful bone tissue engineering, scaffolds with tailored properties are a basic requirement. The combination of different available materials not only appears to be desirable but also very challenging. In this study, a composite material consisting of hydroxyapatite and collagen was produced by a biomimetic precipitation method and characterized by X-ray diffraction (XRD) and thermogravimetry (TGA). Subsequently, a suspension-quick-freezing and lyophilization method was used to incorporate the hydroxyap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…SCs in bone reconstitute the presence of a biocompatible, resorbable, radiolucent, and porous support material with osteoconductive capability that is necessary. 19 Collagen sponges are currently used in various therapeutic practices due to their high availability, secure purification, biocompatibility and non-toxicity. 20 Additionally, their use as a “scaffold” in bone defects has shown positive results whether they are colonized with SCs or not.…”
Section: Discussionmentioning
confidence: 99%
“…SCs in bone reconstitute the presence of a biocompatible, resorbable, radiolucent, and porous support material with osteoconductive capability that is necessary. 19 Collagen sponges are currently used in various therapeutic practices due to their high availability, secure purification, biocompatibility and non-toxicity. 20 Additionally, their use as a “scaffold” in bone defects has shown positive results whether they are colonized with SCs or not.…”
Section: Discussionmentioning
confidence: 99%
“…After the addition of β -TCP, the slurry mixture was stirred for 3 minutes at a speed of 250 rpm. The slurry was casted into a Teflon mold (dimensions 5 mm × 25 mm × 100 mm) and stored at −80°C for 3 hours [ 14 ]. Subsequently, the frozen mixture was lyophilized to obtain a porous collagen/ β -TCP composite.…”
Section: Methodsmentioning
confidence: 99%
“…[1223] These studies have successfully demonstrated deposition of calcium phosphate minerals within a collagen matrix and contributed significantly to the understanding of biomimetic collagen mineralization. Nevertheless, the ability to replicate the intricate patterns of the nanocrystalline assembly at the intrafibrillar level has been elusive.…”
mentioning
confidence: 99%